Origin and composition of the Subcontinental Lithospheric Mantle (SCLM) along the lineament of 125° Azimuth, Brazil - Oliveira, Lynthener Bianca Takenaka de (2022)
The subcontinental lithospheric mantle (SCLM) plays an essential role in tectonic and metallogenetic processes affecting the continental lithosphere. Kimberlitic, kamafugitic and alkaline-carbonatitic (KKAC) magmas are probes of the SCLM; they may carry mantle xenoliths, xenocrysts and ore-forming elements. Over 700 KKAC intrusions are currently identified on the south-western margin of the São Francisco Craton (SWSFC), within the NW-SE lineament of 125° Azimuth (AZ125). However, the ages of the KKAC rocks and the nature of the SCLM are not well established. Moreover, the diamond content in these rocks is very low, while large volumes and individual gems, commonly >100ct, occur in secondary sources. A re-evaluation of the history of the KKAC magmas combines geochronology with mineralogical/chemical characterization of geochronometers. A critical literature review and new ages demonstrate that inherited xenocrysts and primary minerals occur in the same pipes. The compositions of resistate minerals carry clues on their parental magmas, and microstructural/chemical/isotopic features distinguish maximum vs intrusion ages, refining the main KKAC magmatism at 88-76 Ma. Geochemical data from garnet and spinel xenocrysts in the KKAC magmas reveal a SCLM with typical cratonic model geotherms (37.5-42.5 mW/m2 ) and a lithosphere 110-175 km thick; the mean depth for the Base of the Depleted Lithosphere (BDL) is ca 140 km. Ten unidimensional SCLM sections reveal that fertile lherzolites affected by varying degrees of melt-related metasomatism dominate the SCLM; a few depleted SCLM volumes remain both on- and off-craton. A newly recognized traceelement pattern, the Tecton-lherzolite trend, reflects physical mixing between asthenospheric and lithospheric materials in extensional and/or compressional regimes. The perovskite-based oxygen fugacity of KKAC magmas shows relatively low values, where perovskites with FMQ -2 or below probably represent shallow cumulates from deep-seated magmas. A new oxybarometer based on V/Sc in pyrope garnets (V/Scgnt) was calibrated and key trends of fO2 distribution in cratonic, reworked, and Tecton SCLM were defined. Below the SW-SFC, the V/Scgnt trend reflects a SCLM significantly more reduced than cratonic mantle. The chemical tomography is used for interpretation of seismic and MT data. Lithosphere-scale melt/fluid channels controlled the emplacement of magmas that sampled a relatively thin SCLM with large-scale short-range variability in degrees of depletion/fertility. Local differences in lithosphere thickness might explain the large variety of KKAC magmas in the area. The timing of KKAC magmatism in the AZ125, and perhaps in the Lucapa corridor (Angola), may represent a far-field response to the South Atlantic opening. The Archean SCLM below the SW-SFC was progressively modified by several tectonothermal events linked to intense metasomatism and refertilisation, representing craton-margin lithospheric erosion and asthenosphere-SCLM mixing during continental collision and post-rifting continental magmatism. Types I, II and CLIPPIR diamonds found in secondary sources are survivors of those processes, sampled by numerous low-grade, but potentially high-value, KKAC pipes. These findings imply new exploratory paradigms for diamond exploration and perhaps exploration for magmatic ores in the SW-SFC.